Self image: a Christian views himself - Bettler, John F. (Christian Study Services, 1978)
1. Man : everything or nothing? -- 2. How a Christian should view himself I -- 3. How a Christian should view himself II ; Case study I -- 4. Case study I (cont,) and II ; Developing self image in our children -- 5. Delighting in your child.